Hypertension and Other Determinants of White Matter Lesions in Stroke Patients. Issue 9 (28th January 2016) - Muscari, Antonio; Faccioli, Luca; Ghinelli, Marco; Napoli, Chiara; Pirazzoli, Enrico; Puddu, Giovanni M.; Spinardi, Luca; Trossello, Marco Pastore; Zoli, Marco
Abstract : Hypertension is the main risk factor for both white matter lesions (WMLs) and stroke, but many stroke patients do not have WMLs. To find specific determinants of WMLs, the authors assessed 321 ischemic and hemorrhagic stroke patients who had undergone echocardiography. The patients with WMLs (n=160) were more often hypertensive and had a higher systolic blood pressure than the patients without WMLs. However, in a multivariate analysis, only the following variables remained associated with WMLs: (1) age: odds ratio [OR], 1.08 per year (95% confidence interval [CI], 1.06–1.11); (2) left ventricular relative wall thickness (RWT) ≥0.52: OR, 2.78 (95% CI, 1.59–4.88); (3) lacunar strokes: OR, 4.15 (95% CI, 1.83–9.44); (4) hemorrhagic strokes: OR, 5.36 (95% CI, 1.57–18.39); and (5) female: OR, 1.91 (95% CI, 1.12–3.27). Thus, the main modifiable risk factor for WMLs was RWT, which proved to be an even stronger risk factor than hypertension. This suggests that RWT might be a useful target in the treatment of hypertension to counteract the appearance of WMLs.